2019
DOI: 10.1007/s10565-019-09465-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and genomic profiling of pancreatic cancer

Abstract: Pancreatic cancer remains the most fatal human tumor type. The aggressive tumor biology coupled with the lack of early detection strategies and effective treatment are major reasons for the poor survival rate. Collaborative research efforts have been devoted to understand pancreatic cancer at the molecular level. Large-scale genomic studies have generated important insights into the genetic drivers of pancreatic cancer. In the post-genomic era, protein sequencing of tumor tissue, cell lines, pancreatic juice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 80 publications
0
39
0
Order By: Relevance
“…Protein expression patterns in PDAC liver metastases also have the potential to reveal new associations with clinical outcomes or identify novel therapeutic targets (14,31). With the understanding that PDAC is not a singular disease, we hypothesized that associations between protein expression and patient survival might display subtype-specific characteristics.…”
Section: Association Between Individual Protein Expression and Survivmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein expression patterns in PDAC liver metastases also have the potential to reveal new associations with clinical outcomes or identify novel therapeutic targets (14,31). With the understanding that PDAC is not a singular disease, we hypothesized that associations between protein expression and patient survival might display subtype-specific characteristics.…”
Section: Association Between Individual Protein Expression and Survivmentioning
confidence: 99%
“…There have been comparative proteomics studies on PDAC that have identified proteins from tissue, plasma, pancreatic juice, cyst fluid, and urine associated with this disease. These efforts illustrate the potential of applying proteomics approaches to improve early detection and treatment of PDAC based on single proteins (13,14). IHC evaluating expressions of only KRT81 and HNF1A proteins has been used to stratify PDAC tumors as either classical, quasi-mesenchymal, or exocrine-like (15).…”
Section: Introductionmentioning
confidence: 99%
“…Equally, no studies of pancreatic cancer have focused explicitly on segregating the patients based on the proteomic difference, and explored the subtype-specific alterations in the cellular processes and signalling pathways. Furthermore, recent studies have conducted a proteomic analysis of pancreatic cancer [20][21][22][23][24][25][26]; however, they have not integrated the proteomic subtypes with alterations in various signalling pathways, to the specific cancer gene mutations and/or the disease outcomes of the afflicted patients.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of experimental techniques, the number of molecular detection methods for cancer is increasing. These methods play an important role in the early diagnosis of pancreatic cancer [6]. In a previous study, we used two cell lines derived from the hamster model of pancreatic cancer that have distinct invasion and metastasis abilities: a nondissociated, low-metastasis pancreatic cancer cell line (PC-1) and a dissociated, high-metastasis pancreatic cancer cell line (PC-1.0).…”
Section: Introductionmentioning
confidence: 99%